2021
DOI: 10.1177/10547738211033928
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and its Influencing Factors in Community-Dwelling Older Adults With Dementia: A Path Analysis

Abstract: Dementia is prevalent in worldwide, and increases the care burden and potential costs. Physical activity (PA) has been increasingly shown to be beneficial for them. This was a cross-sectional observational study aiming to investigate the status of PA among community-dwelling older adults with dementia in Beijing or Hangzhou, China, and verify the relationships between neuropsychiatric symptoms, activities of daily living (ADL), caregivers’ fear of patients’ falling and their PA using a path analysis approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Nevertheless, research indicates that older adults with dementia/MCI are more prone to physical inactive [ 10 ]. Although numerous studies have explored factors influencing PA in older adults with dementia/MCI [ 11 , 12 ], a recent umbrella review [ 13 ] indicated a scarcity of original research that empirically investigates such factors based on theoretical frameworks, particularly with limited data from developing countries. Moreover, evidence on longitudinal trajectories of PA in older adults with dementia/MCI is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research indicates that older adults with dementia/MCI are more prone to physical inactive [ 10 ]. Although numerous studies have explored factors influencing PA in older adults with dementia/MCI [ 11 , 12 ], a recent umbrella review [ 13 ] indicated a scarcity of original research that empirically investigates such factors based on theoretical frameworks, particularly with limited data from developing countries. Moreover, evidence on longitudinal trajectories of PA in older adults with dementia/MCI is relatively limited.…”
Section: Introductionmentioning
confidence: 99%